Comparison of human tear film osmolarity measured by electrical impedance and freezing point depression techniques - Tomlinson, Alan; McCann, Louise C; Pearce, Edward I (Cornea, 2010)
Tear hyperosmolarity is diagnostic of dry eye disease (DED), yet difficulty in measurement has limited its utility; development of new instruments could facilitate its clinical application. This study compares the new OcuSense TearLab osmometer (OcuSense, Inc, San Diego, CA), based on electrical impedance "lab-on-a-chip" nanoliter technology, with the freezing point depression Clifton Osmometer (Clifton Technical Physics, Hartford, NY). Thirty-six subjects were recruited: 15 DED (9 women, 6 men age: 41 +/- 16 years) and 21 controls (12 women, 9 men age: 35 +/- 12 years); criteria for DED were noninvasive tear breakup time <10 seconds, Schirmer I test <5 mm, and positive symptoms. Samples were collected from the inferior tear meniscus for testing with both osmometers. Osmolarity values measured with OcuSense TearLab were 308 +/- 6 and 321 +/- 16 mOsm/L for controls and dry eye, respectively, and those measured with Clifton were 310 +/- 7 and 323 +/- 14 mOsm/L for controls and dry eye, respectively; these values were significantly different. Significant correlation was found between OcuSense and Clifton measurements (r = 0.904; P = 0.006). Bland-Altman analysis revealed agreement between techniques; the majority of points fell within the 95% confidence limits, and actual values differed by less than 1%. A cutoff value of >316 mOsm/L, derived from the distribution of osmolarity values, was used to diagnose DED with an effectiveness of 73% sensitivity, 90% specificity, and 85% positive predictive value for the OcuSense and 73% sensitivity, 71% specificity, and 65% positive predictive value for the Clifton in the study samples. Tear film osmolarity measured with the OcuSense TearLab system correlates well with the Clifton Osmometer. The new instrument has the potential to provide clinicians with a readily available clinically applicable measure, which could become the gold standard in DED.